Emergy evaluation of a traditional farming system. Case study: Leh District (Ladakh - Indian Trans-Himalaya) - Pelliciardi, Vladimiro; Varvaro, Leonardo; Maria Pulselli, Federico (European Journal of Sustainable Development, 2014)
Ladakh traditional farming system has been included on the F.A.O. list of possible “Globally Important Agricultural Heritage Systems”, worthy of being preserved and conserved. The paper describes and assesses cultivation practices in a typical familymanaged farm, located in central Ladakh, analysing how natural resources are exploited, conserved and recycled. Emergy evaluation, an environmental accounting methodology, has been applied to evaluate and compare five staple crop productions: barley, wheat, pea, mustard, and fodder alfalfa. Unit Emergy Values of products (UEV, emergy per unit product, a measure of the environmental production cost) are calculated, taking into account the inputs to production such as water from glaciers, soil fertility, human and animal labour, and more. Results show that the traditional agricultural practices in Ladakh, completely supported by renewable flows, are efficient in the use of local resources. In fact, the UEVs of agroproducts are similar to those of analogous products of conventional agriculture (e.g. 5.27E+05 and 6.64E+05 semj/J for barley and wheat in Ladakh, respectively; 7.37E+05 semj/J for corn in USA), though the inputs of Ladakh agriculture are strongly limited in type and quantity. At the same time, local farmers can create, maintain and rebuild soil functions whose UEV is 1.62E+07 semj/J. Keywords: Ladakh, agrosystem, emergy, environment, sustainability